Expression of a Human Caveolin-1 Mutation in Mice Drives Inflammatory and Metabolic Defect-Associated Pulmonary Arterial Hypertension - Rathinasabapathy, Anandharajan; Copeland, Courtney; Crabtree, Amber; Carrier, Erica J.; Moore, Christy; Shay, Sheila; Gladson, Santhi; Austin, Eric D.; Kenworthy, Anne K.; Loyd, James E.; Hemnes, Anna R.; West, James D. (Frontiers in Medicine, 2020)
Background: In 2012, mutations in Cav1 were found to be the driving mutation in several cases of heritable pulmonary arterial hypertension (PAH). These mutations replaced the last 21 amino acids of Cav1 with a novel 22 amino acid sequence. Because previously only Cav1 knockouts had been studied in the context of PAH, examining the in vivo effects of this novel mutation holds promise for new understanding of the role of Cav1 in disease etiology. Methods: The new 22 amino acids created by the human mutation were knocked into the native mouse Cav1 locus. The mice underwent hemodynamic, energy balance, and inflammatory measurements, both at baseline, and after being stressed with either a metabolic or an inflammatory challenge (low dose LPS). To metabolically challenge mice, they were injected with streptozotocin (STZ) and fed a high fat diet for 12 weeks. Results: In vivo, very little mutant protein was found (roughly 2% of wild-type by mass-spectrometry), probably because of degradation after failure to traffic from the ER. Homozygous mutants developed a mild, low-penetrance PAH similar to that described previously in knockouts, and neither baseline nor metabolic nor inflammatory stress resulted in pressures above normal in heterozygous animals. Homozygous mutants had increased lean mass and worsened oral glucose tolerance, as previously described in knockouts. Novel findings include preservation of Cav2 and accessory proteins in liver and kidney, while they are lost with homozygous Cav1 mutation in lungs. We also found that homozygous had significantly lower tolerance to voluntary spontaneous exercise tolerance than wild-type mice, with heterozygous at an intermediate level. Mutants also had higher circulating monocytes, with both heterozygous and homozygous animals having higher pulmonary MCP1 and MCP5 protein. Heterozygous also lost weight at an LPS challenge level at which wild-type mice continued to gain weight. Conclusions: The Cav1 mutation identified in human patients in 2012 is molecularly similar to a knockout of Cav1. It results in metabolic deficiencies and mild pulmonary hypertension, as expected, but also an inflammatory phenotype and reduced spontaneous exercise.